2023
DOI: 10.1161/atvbaha.122.318451
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 (Methyltransferase Like 3)-Dependent N6-Methyladenosine Modification on Braf mRNA Promotes Macrophage Inflammatory Response and Atherosclerosis in Mice

Abstract: BACKGROUND: Atherosclerosis is a chronic inflammatory disease, in which macrophages determine the progression of atherosclerotic plaques. However, no studies have investigated how METTL3 (methyltransferase like 3) in macrophages affects atherosclerotic plaque formation in vivo. Additionally, whether Braf is modified by METTL3-dependent N6-methyladenosine (m6A) methylation remains unknown. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our results showed that the expression of METTL3 was significantly increased in the aorta of AS mice, which is consistent with a previous study [ 18 ]. Furthermore, METLL3 silencing could hamper atherosclerotic plaque formation by targeting JAK2/STAT3 pathway or Braf mRNA, indicating the critical role of RNA methylation in AS progression [ 19 , 20 ], although the underlying molecular mechanism, deserves further investigation. Another study has demonstrated that the expression of FTO was significantly decreased in the human carotid artery plaques of early atherosclerosis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the expression of METTL3 was significantly increased in the aorta of AS mice, which is consistent with a previous study [ 18 ]. Furthermore, METLL3 silencing could hamper atherosclerotic plaque formation by targeting JAK2/STAT3 pathway or Braf mRNA, indicating the critical role of RNA methylation in AS progression [ 19 , 20 ], although the underlying molecular mechanism, deserves further investigation. Another study has demonstrated that the expression of FTO was significantly decreased in the human carotid artery plaques of early atherosclerosis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lactic acid facilitated M2 polarization by activating METTL3 via the Trib1/ERK/STAT3 pathway [ 209 ]. Knockdown of METTL3/METTL14 significantly inhibited macrophage activation and secretion and slowed the progression of liver fibrosis [ 210 , 211 ]. Additionally, WTAP and RBM15 interact with M1 macrophages and mediate downstream inflammatory responses [ 212 ] (Fig.…”
Section: Classification Of Rna Methylationmentioning
confidence: 99%
“…Similarly, METTL3 promoted oxLDL-induced macrophage inflammatory response via the m6A modification of Stat1 and Braf mRNA, explaining the observation that oxLDL enhanced m6A modification of macrophage mRNA. METTL3 also interacted with STAT1 protein to promote transcription of macrophage inflammatory factors [33,34]. However, decreased m6A modification of macrophage RNA in response to oxLDL has been reported, mediated by Matrin-3 (Matr3) which enhanced the formation of the METTL3-METTL14 complex.…”
Section: Erasersmentioning
confidence: 99%
“…The diverse reported patterns in oxLDL-stimulated macrophage m6A may be attributed to the different cell models (RAW264.7 and THP-1) and detection techniques (dot blot and flow cytometry) used [33][34][35]. Further investigations, including assessment of cell models and detection techniques, are necessary to establish whether m6A modification promotes or inhibits AS and molecular mechanisms involved.…”
Section: Erasersmentioning
confidence: 99%